A new species of Orobdella (Hirudinida: Arhynchobdellida: Orobdellidae) from Primorye Territory, Russian Far East. Issue 5 (9th February 2019) - Nakano, Takafumi; Prozorova, Larisa
ABSTRACT: A quadrannulate leech species, Orobdella ghilarovi sp. nov., from Primorye Territory in the southern Russian Far East is described. Phylogenetic analyses using nuclear 18S rRNA, 28S rRNA, histone H3, mitochondrial cytochrome c oxidase subunit I, tRNA Cys, tRNA Met, 12S rRNA, tRNA Val, 16S rRNA, tRNA Leu and NADH dehydrogenase subunit 1 markers showed that O. ghilarovi forms a fully supported clade with a monophyletic lineage comprising two species, O. kawakatsuorum and O. koikei, inhabiting Hokkaido, Japan. Quadrannulate Orobdella leeches distributed in the southern Primorye Territory have been identified as O. whitmani, which was originally described in Japan; these past records should be amended based on the taxonomic conclusions of this study. http://zoobank.org/urn:lsid:zoobank.org:pub:8D91AC1C-5868-4F0B-A09D-423F7B50206C